Strength and conditioning for combat sports athletes - Franchini, Emerson; Herrera-Valenzuela, Tomás (Revista de Artes Marciales Asiáticas, 2021)
Editors Emerson Franchini – University of São Paulo, São Paulo (Brazil) Tomás Herrera-Valenzuela – Universidad de Santiago de Chile (Chile) Authors Ursula Ferreira Julio – University of São Paulo, São Paulo (Brazil) Emerson Franchini – University of São Paulo, São Paulo (Brazil) Tomás Herrera-Valenzuela – Universidad de Santiago de Chile (Chile) João Paulo Lopes-Silva – CESMAC University Centre (Brazil) Braulio Henrique Magnani Branco – Cesumar University (Brazil) Jonatas Ferreira da Silva Santos – Federal University of the Jequitinhonha and Mucuri Valleys (Brazil) Rubens Santos-Junior – State University of Pará (Brazil) Reviewers Filipa Almeida – Universidad de Granada (Spain) Juan Bonitch Góngora – Universidad de Granada (Spain) Eduardo Carballeira Fernández – Universidade da Coruña (Spain) Daniele Detanico – Universidade Federal de Santa Catarina (Brazil) Raquel Escobar Molina – Universidad de Granada (Spain) Matheus Hausen – Brazil Olympic Committee (Brazil) Raquel Hernandez García – Universidad de Murcia (Spain) Eliseo Iglesias Soler – Universidade da Coruña (Spain) Carlos Montero Carretero – Universidad Miguel Hernández (Spain) Emanuela Pierantozzi – Università degli Studi di Genova (Italy) Luis Santos Rodríguez – Universidad de León (Spain) Jozef Simenko – University of Essex (UK)